Critical Illness Is Associated With Impaired Gallbladder Emptying as Assessed by 3D Ultrasound. Issue 9 (September 2016) - Plummer, Mark P.; Kar, Palash; Cousins, Caroline E.; Hausken, Trygve; Lange, Kylie; Chapman, Marianne J.; Jones, Karen L.; Horowitz, Michael; Deane, Adam M.
Abstract : Objective: To quantify gallbladder dysfunction during critical illness. Design: Prospective observational comparison study of nutrient-stimulated gallbladder emptying in health and critical illness. Setting: Single-centre mixed medical/surgical ICU. Patients: Twenty-four mechanically ventilated critically ill patients suitable to receive enteral nutrition were compared with 12 healthy subjects. Interventions: Participants were studied after an 8-hour fast. Between 0 and 120 minutes, high-fat nutrient (20% intralipid) was infused via a postpyloric catheter into the duodenum at 2 kcal/min. Measurements and Main Results: Three-dimensional images of the gallbladder were acquired at 30-minute intervals from –30 to 180 minutes. Ejection fraction (%) was calculated as changes between 0 and 120 minutes. Blood samples were obtained at 30-minute intervals for plasma cholecystokinin. Data are mean (SD) or median [interquartile range]. In the critically ill, fasting gallbladder volumes (critically ill, 61 mL [36–100 mL] vs healthy, 22 mL [15–25] mL; p < 0.001] and wall thickness (0.45 mm [0.15 mm] vs 0.26 mm [0.08 mm]; p < 0.001] were substantially greater, and sludge was evident in the majority of patients (71% vs 0%). Nutrient-stimulated emptying was incomplete in the critically ill after 120 minutes but was essentially complete in the healthy individuals (22 mL [9–66 mL] vs 4 mL [3–5 mL]; p < 0.01]. In five critically ill patients (21%), there was no change in gallbladder volume in response to nutrient, and overall ejection fraction was reduced in the critically ill (50% [8–83%] vs 77 [72–84%]; p = 0.01]. There were no differences in fasting or incremental cholecystokinin concentrations. Conclusions: Fasted critically ill patients have larger, thicker-walled gallbladders than healthy subjects and nutrient-stimulated gallbladder emptying is impaired with "gallbladder paresis" occurring in approximately 20%. Abstract : Supplemental Digital Content is available in the text.